Giant chondrosarcoma of the sternal body: case report - José Dalvo Maia; Antero Gomes; Ryan Nogueira Lima; Maria de Fátima de Brito Coutinho Nogueira Lima (Revista Brasileira de Cirurgia Plástica)
Chest wall tumors are relatively uncommon, representing 1 to 2% of all neoplasms, and approximately 5% of thoracic neoplasms. Sarcomas are rare tumors with heterogeneous presentation. They are divided into two large groups: bone and soft tissue tumors. Occurrence in the chest wall is rare, representing 8% of all sarcomas. The treatment of choice is resection with wide margins and, when invasion of deep structures occurs, thoracotomy is indicated. The reconstruction of the bone framework is carried out with synthetic materials, providing stability, and is followed by the reconstruction of soft tissues with muscular, musculocutaneous, or random local flaps. Primary malignant tumors of the chest wall account for less than 1% of all neoplasms and include a wide variety of bone and soft tissue lesions. Chondrosarcomas represent 20% of primary tumors of the chest wall, with 80% originating in the ribs and 20% in the sternum.